The Real Picture of Professional Multidimensionality - Yalalov, Farit G.; Bordovsky, Gennady A.; Kouznetsov, Dennis V. (Journal of History Culture and Art Research, 2017)
Professional multidimensionality is ability of a specialist to correlate the directions, approaches (integrity) and/or to combine performance of several functions (multifunctionality), to conjoin the simultaneous solution of several tasks (multitasking). The empirical research on identification of a real picture of professional multidimensionality of specialists in three fields of activity was performed by research associates group of the Nizhnekamsk office of UNESCO department at A.I. Herzen Russian State Pedagogical University under the leadership of the authors of this article. In their professional activity specialists most often apply such basic multidimensional competences as multifunctionality, multitasking and integrity. Empirical experiment covered 180 representatives of different spheres of professional activity. On the basis of experimental studies we received the following results. Rather high level of professional multidimensionality is shown by research associates – 27,9% of them possess multifunctionality, 23,3% – multitasking, 18,6% – integrity, 13,8% – the combined multidimensional competences. Among elementary school teachers professional multidimensionality is demonstrated thus: 21,1 % of them show multifunctionality, 24,7% – multitasking, 15,3% – integrity, 7.2% – the combined multidimensional competences. Professional multidimensionality among drivers of buses is demonstrated thus: 15,4 % of them possess multifunctionality, 13,5% – multitasking. Drivers of buses show absence of integrity and the combined multidimensional competences.